2010
DOI: 10.2341/08-065-l
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Warm Air Stream for Solvent Evaporation: Effects on the Durability of Resin-dentin Bonds

Abstract: This study evaluated the effect of a warm (W) or cold (C) air-dry stream for solvent evaporation on the immediate (IM) and six-month (6M) resindentin bond strength (µTBS) and silver nitrate uptake pattern (SNU) of two-step etch-and-rinse adhesive system (Adper Single Bond [SB] and Prime & Bond 2.1 [PB]). The adhesives were applied on demineralized dentin surfaces and a warm or cold air-dry stream (10 seconds) was applied followed by light-activation (10 seconds). After 24-hours of water storage, the specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 37 publications
(40 reference statements)
1
43
1
3
Order By: Relevance
“…No significant differences in microtensile bond strength were found among the groups tested in the present study. This finding contradicts some reports indicating that increased adhesive temperature immediately improves bond strength, regardless of the heating device or protocol used 18,19 . This discrepancy may be explained by the possibility that the temperature increase promoted by the light-curing unit itself could have been enough to improve the physicochemical reactions and enhance monomeric permeation into the etched dentin 16,[20][21][22] .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…No significant differences in microtensile bond strength were found among the groups tested in the present study. This finding contradicts some reports indicating that increased adhesive temperature immediately improves bond strength, regardless of the heating device or protocol used 18,19 . This discrepancy may be explained by the possibility that the temperature increase promoted by the light-curing unit itself could have been enough to improve the physicochemical reactions and enhance monomeric permeation into the etched dentin 16,[20][21][22] .…”
Section: Discussioncontrasting
confidence: 56%
“…A warming protocol presented in the literature as an option for in vitro tests has been found to increase bond strength values 24 . Since heating promotes a forced evaporation of the solvent, it can alter the stoichiometric balance of the adhesive, thus affecting its permeation capability into the etched dentin 10,19 . However, despite these advantages, warm air applied to heat up adhesives up to 20°, 30°, and 50°C has failed to increase bond strength values in a previous study 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, all solvents should be completely removed from the dentin surface prior to polymerization. One clinical approach to obtaining stable dentin bonding and relatively higher bond strengths is to employ warm air-drying of the adhesives 4,5) . However, complete evaporation using with dental air syringe in clinical situations is diffi cult to achieve and is dependent on the properties of the solvents 6) .…”
Section: Introductionmentioning
confidence: 99%
“…2-3 Over the last decade, a number of investigations have reported that several factors might interfere with the bonding ability of adhesive systems to enamel or dentin, including the adhesion strategy, 4 conditioning time, 5 solvent removal method, [6][7] thickness of the adhesive layer, 8 substrate structure 9 and even the provisional restorative material previously used. [10][11][12][13][14][15] Among the provisional restorative materials, zinc oxide eugenol (ZOE) is widely used as a temporary material during endodontic treatments and restorative dentistry due to its sedative effect on sensitive teeth, its low cost, ease of removal and proper seal against leakage.…”
Section: Introductionmentioning
confidence: 99%